Motivation to learn : integrating theory and practice - Stipek, Deborah J. (Boston : Allyn and Bacon, 2002)
Stipek (education, Stanford U.) provides a clear discussion of motivation theories and research and their implications for educational practice. Emphasizing classroom learning, she also discusses how strategies used to motivate students in schools affect students' motivation to engage in intellectu .
Includes bibliographical references.
Keywords: Motivation in education; Achievement motivation in children; Learning, Psychology of